Utilization of hydroxyprogesterone caproate among pregnancies with live birth deliveries in the sentinel distributed database. (12th December 2022) - Shinde, Mayura; Cosgrove, Austin; Woods, Corinne M.; Chang, Christina; Nguyen, Christine P.; Moeny, David; Ajao, Adebola; Kolonoski, Joy; Tsai, Huei-Ting
Abstract: Background: The U.S. Food and Drug Administration (FDA) approved Makena ® (hydroxyprogesterone caproate [HPC] injection) in February 2011 for reducing the risk of preterm birth (PTB) in women with a singleton pregnancy who had a history of singleton spontaneous PTB (sPTB). Makena was approved under accelerated approval and required a postmarketing study to verify its clinical benefits. However, the postmarketing trial (PROLONG) failed to verify Makena's clinical benefit to neonates and substantiate its effect on reducing the risk of recurrent PTB. This study examined the utilization of HPC, along with another progestogen (vaginal progesterone) used to reduce the risk of sPTB during pregnancy, to inform the landscape of HPC use in the United States. Methods: We included pregnant women aged 10–54 years with a live birth delivery from 1 January, 2008 to 31 December, 2018 in the Sentinel Distributed Database (SDD). We examined the prevalence of injectable HPC (Makena and its generics), compounded HPC, and vaginal progesterone use during the second and third trimesters during the study period. We also assessed the proportion of these HPC-exposed pregnancies with obstetrical conditions of interest as potential reasons for use: (1) history of preterm delivery; (2) cervical shortening in the current pregnancy; and (3) preterm labor in the current pregnancy. Results: We identified a total of 3, 445, 739 live-birth pregnancies (among 2.9 million women) between 2008 and 2018 in the SDD. Of these pregnancies, 6.5 per 1, 000 pregnancies used injectable HPC, 2.3 per 1, 000 pregnancies used compounded HPC, and 1.5 per 1, 000 pregnancies used vaginal progesterone during the second and/or third trimesters. The yearly uptakeof pregnancies with injectable HPC use increased during the study period from 2.1 per 1, 000 pregnancies in 2012 to 12.6 per 1, 000 pregnancies in 2018; use of compounded HPC decreased from 3.3 per 1, 000 pregnancies to 0.25 per 1, 000 pregnancies over the same period. Of 16, 524 pregnancies with injectable HPC use, 12, 054 (73%) had at least one related obstetrical condition, including 6, 439 (39%) with a recorded history of preterm delivery. In addition, 4, 665 (28%) had a PTB recorded as the outcome for the current pregnancy. Conclusions: We found modest use of HPC during the second and/or third trimesters among all live-birth pregnancies in SDD. The majority of pregnancies with injectable HPC use had at least one of three obstetrical indications of interest recorded before or during the pregnancy.